NATO Has Been Called Greatest Threat to World Peace—Now Biden Plans Dangerous Expansion That Will Increase Military Spending and Escalate the Risk of War (CovertAction Magazine, 2021)
Biden calls support for NATO a “sacred obligation” as he raises false alarms about alleged military threats from Russia and China.